Internet usage as a learning tool among Malaysian universities students (Journal of Business Management and Accounting, 2012)
The study examined the factors influencing the usage of the Internet for academic purposes amongst final year business students in public universities in Malaysia. The research model employed the variables from the theory of acceptance model (TAM), namely perceived usefulness, perceived ease of use, intention, and behavior. A structured, self-administered questionnaire was used to elicit responses from a randomly selected sample of 422 respondents. Regression analyses were employed to analyze the data. The results indicated that perceived ease of use had an effect on the perceived usefulness (at the R2 value of 0.14), which in turn influenced students’ intention to use the Internet for academic purposes. In addition, with a significant â value of 0.367, perceived usefulness was also found to mediate the impact of perceived ease of use on students’ intention to use the Internet. Finally, intention was also found to influence the actual behavior at 45 percent. In view of the results, it can be concluded that the Internet application is a useful tool to assist students’ learning. Thus, academicians should be open and opportunistic in applying this dynamic tool in their teaching.